Tyre Safety Performance on Asphalt Pavement in Malaysia Climate - Analysis through Finite Element Method - A. H., Sufian; A. S., Jamaludin; A. N., Ibrahim; M. N., Mhd Razali; M. S., Osman; S. B., Hamzah (Society of Automotive Engineers Malaysia, 2019)
Interaction characteristics between tyre and asphalt pavement surface are one of the important aspects that need to be taken into consideration in maintaining the safety of driving through increasing the effectiveness of tyre and optimizing the possibility of skidding, especially during hydroplaning conditions. Lower quality of tyres in terms of tyre life, bad tyre rethreading, low tyre material quality plus lack of awareness by road users can be considered the main factors in occurrence of car accidents in Malaysia. The study is done on the contact performance between tyre surface and asphalt pavement in hot and humid Malaysia climate, with the application of Finite-Element Method. In maintaining or increasing the safety features of tyre, several parameters such as rotational speed, vehicle weight, tyre-road contact friction will be studied through computer simulation. It is estimated that increment of loading, surface contact between tyre and road pavement will increase, thus increasing the frictional contact. It is shown that effective frictional characteristic is needed, where traction, braking, life of tyre can be optimized